KAJIAN PENANGGULANGAN BANJIR PADA KAWASAN JALAN AHMAD YANI DIKELURAHAN TANGGATAKAT KECAMATAN SEBERANGULU II PALEMBANG - Awaluddin, Muhammad; Yunus, Ishak; Syaifudin, Achmad (Jurnal Teknik Sipil, 2018)
A decent and comfortable City for residence should have some life support infrastructure is infrastructure of drainage system. And it is well known that the drainage function in a scope of the urban environment is urgently needed in the drain surface water and puddle to tributaries or to retention. Flood or standing in a region still many settlements occurred in the city of Palembang. One of the areas that are often experienced a flood is the Ahmad Yani Village opposite the Ulu Subdistrict Point Ladder II. Method for calculating of flood discharge was approached by rational formulas, and rainfall data taken from the station Climatology class II Kenten. In analyzing the magnitude of rainfall intensity using equation mononobe. It starts with an understanding of the problem, the study of the literature relating to the problem so that the author can better understand these problems, data collection both primary and secondary data, dilanjukan by analyzing data that have become available so that the results obtained from the analysis of which will then be discussed. Existing conditions Drainage Channels In the region the way Ahmad Yani has the dimensions i.e. width 1.68 m and height channels 0.73 m, the magnitude of the 1.690 channel capacity m3/s, Debit Draft at the region the way Ahmad Yani in the village opposite the Ulu Subdistrict Point Ladder II Palembang with Period 2 year anniversary with debit flood 2.16 m3/s, 5 years with debit flood 2.94 m3/s , 10 years with debit flood 3.45 m3/s, with a 25-year flood discharge 4.10 m3/s, with a 50-year flood discharge 4.59 m3/sec and 100-year flood discharge with 5.07 m3/s, based on the results of the analysis of channel capacity (existing) do not meet or are not able to accommodate flood discharge, re-planning needs to be done so that the dimensions of the channel